1998
DOI: 10.1021/jp980675c
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Property of FSM-16

Abstract: Siliceous FSM-16 possesses acid sites to catalyze but-1-ene isomerization to produce but-2-ene (cis/trans ) 1.4-1.7) at 323 K and 2,6,6-trimethylbicyclo[3.1.1]hept-2-ene (R-pinene) isomerization at 303 K. Catalytic activity was dependent upon heat treatment and reached a maximum at 673 K. The maximum acid strength was invariably H 0 ) -3.0 independent of the pretreatment temperatures. The acidity was much reduced by calcination at higher temperatures, but restored by water treatment at 353 K as long as the FSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 67 publications
(98 reference statements)
10
112
0
Order By: Relevance
“…The ability of a siliceous mesoporous structure similar to MCM-41 (FSM-16), to catalyze the isomerization of α -pinene was already reported by Yamamoto et al [31].…”
Section: Catalytic Testsmentioning
confidence: 90%
See 1 more Smart Citation
“…The ability of a siliceous mesoporous structure similar to MCM-41 (FSM-16), to catalyze the isomerization of α -pinene was already reported by Yamamoto et al [31].…”
Section: Catalytic Testsmentioning
confidence: 90%
“…4A (150 ºC). The spectra display bands at 1547 and 1639 cm -1 assigned to pyridine adsorbed on Brönsted acid sites, bands at 1454 and 1621 cm -1 assigned to pyridine adsorbed on Lewis acid sites and a band at 1491 cm -1 characteristic of pyridine adsorbed on both sites [31]. The spectra of AlMCM-41 and MSU-S(MFI) show further bands at 1445 and 1598 cm -1 that have been assigned to H-bonded pyridine [31] or to a pyridine molecule adsorbed on a Lewis acid site and interacting through hydrogen bonding with a protonic site [32].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…For example, the greater surface areas such as 815 1078 m 2 /g supplied by Toyota Central R & D labs, Inc. (Lot no. NG78-550), 14) as well as 1070 and 1100 m 2 /g prepared by Inagaki et al 8) were reported. The samller surface area of FSM-16 prepared in the present study would indicate that it contains tridymite as impurities.…”
Section: Characterization Of Fsm-16 and Cr-fsm-16mentioning
confidence: 92%
“…We independently found that siliceous mesoporous silica FSM-16 promoted some acid catalyzed reactions, and have been investigating the acidic properties of FSM-16. We proposed that weakly perturbed silanol groups on the surface of the specific hexagonally ordered pore structure with thin wall act as Brønsted acid sites, with medium strength of H0 3.0 41) , and strained siloxane bridges formed by dehydration of isolated silanol groups act as the Lewis acid site 42) . The catalytic activity for 2-butanol dehydration was found to depend on pore size of FSM-16 in the range of 1.8 to 3.8 nm (Fig.…”
Section: )mentioning
confidence: 99%